Looking for reliable answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Discover comprehensive solutions to your questions from a wide network of experts on our user-friendly platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.

Solve the system by substitution. 2x - y = -3, 2x-2y = -2

Sagot :

Answer:// Solve equation [1] for the variable  y

 [1]    y = 2x - 3

// Plug this in for variable  y  in equation [2]

  [2]    -2•(2x-3) + 2x = 2

  [2]     - 2x = -4

// Solve equation [2] for the variable  x

  [2]    2x = 4

  [2]    x = 2

// By now we know this much :// Solve equation [1] for the variable  y

 [1]    y = 2x - 3

// Plug this in for variable  y  in equation [2]

  [2]    -2•(2x-3) + 2x = 2

  [2]     - 2x = -4

// Solve equation [2] for the variable  x

  [2]    2x = 4

  [2]    x = 2

// By now we know this much :

   y = 2x-3

   x = 2

// Use the  x  value to solve for  y

   y = 2(2)-3 = 1

   y = 2x-3

   x = 2

// Use the  x  value to solve for  y

   y = 2(2)-3 = 1

Step-by-step explanation: